Study of the Effects of Service Quality Variables on Customer Satisfaction and Loyalty - Halika, Nurma; Kharisma, Kiran (Journal of Social Science and Business Studies, 2024)
This research aims to explore the influence of service quality variables on customer satisfaction and loyalty. Adoption of an explanatory survey type was the research method chosen, with a sampling technique that involved identifying customers who regularly visit at least three times a month. A total of 100 respondents were collected during the research using quantitative analysis methods through structural equation modeling (SEM). The research results show that service factors such as tangibility, reliability, responsiveness, and assurance have a significant influence on customer satisfaction. The research results indicate that service quality plays a crucial role in shaping consumer satisfaction, as evidenced by the significant relationships found between service variables and customer satisfaction. Furthermore, customer satisfaction significantly influences customer loyalty. Furthermore, reliability, responsiveness, assurance, and empathy have also been proven to significantly impact customer loyalty. Overall, the research findings indicate that tangible, reliability, responsiveness, assurance, and empathy together influence customer loyalty through customer satisfaction. The importance of the direct influence of service factors on customer loyalty is emphasized with greater value compared to the indirect influence through customer satisfaction. These results illustrate the positive contribution of direct service aspects to forming customer loyalty through increasing satisfaction levels in the restaurants studied.